Holocene history of landscape development in the catchment of Lake Skogstjern, southeastern Norway, based on a high-resolution multi-proxy record. (December 2017) - Wieckowska-Lüth, Magdalena; Kirleis, Wiebke; Doerfler, Walter
A high-resolution multi-proxy record from sediments of a small-sized lake situated in Telemark, southeastern Norway, was used to reconstruct the local landscape development of the past c. 10, 500 years. Our data demonstrate that changes in vegetation composition and structure in the first two-thirds of the Holocene are principally attributable to climatic changes and high erosion rates, as deduced from geochemical and physical (loss-on-ignition) proxy analyses. The highest signals of erosional inputs to the lake (c. 8030–5760 cal. BP) can be correlated with the first part of the Holocene Thermal Maximum. Nevertheless, evidence from pollen, non-pollen palynomorphs and microscopic charcoal analyses indicates the presence of nutrient-rich and disturbed environments already during the middle Mesolithic (c. 10, 050–9400 cal. BP). It also shows traces of animal husbandry (c. 5580 cal. BP) and small-scale cereal cultivation (c. 5520 cal. BP) in the early Neolithic. In subsequent periods, human impact remains at a relatively low level and does not generate significant palaeo-environmental changes. Not until the second half of the Bronze Age (c. 2840 cal. BP) is some intensification in animal husbandry recorded, whereas crop cultivation continues to play a minor role in the second millennium BP. The establishment of a full farming economy took place during the Roman Iron Age (c. 1790 cal. BP), characterised by extensive forest clearance and local fires, crop cultivation in permanent fields and the presence of open pastures. This establishment is associated with advanced soil degeneration and increased erosion rates.